Association Between Endometriosis and Mental Disorders Including Psychiatric Disorders, Suicide, and All-Cause Mortality -A Nationwide Population-Based Cohort Study in Taiwan - Wang TM; Lee YL; Chung CH; Sun CA; Kang CY; Wu GJ; Chien WC (International Journal of Women's Health, 2023)
Tsan-Min Wang,1 Yi-Liang Lee,2,3 Chi-Hsiang Chung,1,4,5 Chien-An Sun,6,7 Chieh-Yi Kang,8 Gwo-Jang Wu,1,2,9 Wu-Chien Chien1,4,5,10 1Department of Medical Research, Tri-Service General Hospital, Taipei, 11490, Taiwan; 2Department of Obstetrics and Gynecology, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan, Republic of China; 3Department of Obstetrics and Gynecology, Kang Ning Hospital, Taipei, Taiwan, Republic of China; 4School of Public Health, National Defense Medical Center, Taipei, 11490, Taiwan; 5Taiwanese Injury Prevention and Safety Promotion Association (TIPSPA), Taipei, 11490, Taiwan; 6Department of Public Health, College of Medicine, Fu-Jen Catholic University, New Taipei City, Taiwan, Republic of China; 7Big Data Research Center, College of Medicine, Fu-Jen Catholic University, New Taipei City, Taiwan, Republic of China; 8Department of Obstetrics & Gynecology, Chi Mei Medical Center Gynecologic Oncologist Division, Tainan City, Taiwan, Republic of China; 9Graduate Institute of Medical Sciences, National Defense Medical Center, Taipei, 11490, Taiwan; 10Graduate Institute of Life Sciences, National Defense Medical Center, Taipei, 11490,TaiwanCorrespondence: Wu-Chien Chien; Gwo-Jang Wu, Email chienwu@ndmctsgh.edu.tw; gwojang@yahoo.comObjective: A multitude of previous studies has substantiated that endometriosis correlated highly with psychiatric health. This study aims to investigate the association between endometriosis and psychiatric health.Methods: Utilizing the National Health Insurance Research Database of Taiwan, 100,770 enrolled participants, including 20,154 patients with endometriosis and 80,616 in the control group (1:4), matched for age, and index date from Taiwan’s Longitudinal Health Insurance Database between January 1, 2000, and December 31, 2015. The Cox proportional regression model was used to compare the risk of mental disorders during the 16 years of follow-up after adjusting for confounding factors.Results: Of the study patients, 4083 (20.26%) developed mental disorders; 9225 of the 80,616 controls (11.44%) developed mental disorders. The Cox regression demonstrated that, after adjusting for age, monthly income, urbanization level, etc., people with endometriosis are more likely to suffer from mental disorders compared to those without endometriosis (hazard ratio [HR]=2.131; 95% confidence interval [CI]= 1.531– 2.788; p< 0.001). The result illustrated that women over 40 years old had a more significant risk.Conclusion: Compared to people without endometriosis, this study provides evidence that patients with endometriosis are at a 2.131-fold higher risk of developing mental disorders, especially in elder women. Regular psychiatric follow-up might be needed for those patients.Keywords: endometriosis, mental disorders, national health insurance research database, cohort study, Taiwan, women